Análise espaço-temporal do desmatamento no estado do Maranhão no período 1986-2023 - BASSON, Lidielze Oliveira Dourado (2024)
The expansion and cerelity of environmental impacts due to the advance of deforestation has been responsible for the degeneration of natural domains, affecting the entire environmental dynamics at different geographical scales. In the territory of Maranhão, deforestation has been causing significant reductions in the Cerrado and Amazon biomes, in different proportions. Based on this assumption, the work aimed to analyze the deforestation pattern and its effects on the environmental dynamics of the State of Maranhão, in the areas of the Amazon and Cerrado biome from the Forest and Non-Forest categories. The quantification of deforestation was carried out based on the analysis of use, cover, and deforestation data from Mapbiomas and data extracted from satellite images in a temporal analysis from 1985 to 2023. The research revealed that deforestation follows a historical process with different realities and intensities. In the Amazon biome, livestock had consecutive growth in most of the series, however, in the cerrado biome, the livestock area had a greater advance, reaching a higher percentage in 2023. The second activity that has been advancing in the state is soybeans, in which it has been gaining relevance from the year 1990 to the present day, covering mainly the area of the cerrado biome. Silviculture occupies relevant areas from 1988, when it was analyzed in the biomes, it was identified that in the cerrado the activity has been going on since 1986. Such activities favored the reduction of biome areas, the Forest area had a loss of 56.25% and the Non-Forest natural area lost 29.01% in the State. As for deforestation in the territory of Maranhão, it was observed that in the forest area deforestation occurred in greater proportion in the first years of the time series, however, despite the reduction presented in some years, in 2023 it showed an increase of 21.11% compared to 2022. In the Non-Forest natural area, the reality was the opposite, in the first years of the series deforestation was lower, but it has been gradually increasing, with higher percentages in the years 2020, 2022 and 2023. Deforestation is linked to several impacts, among which the work exposed the loss of biodiversity, rainfall disturbances, the increase in temperature, which consist of climatic extremes, which are mainly linked to CO² emissions. In the state, emissions are the result, in the first place, of the change in land and forest use, followed by agricultural activity, placing the state in 9 th place in emissions in the series analyzed. Thus, it is necessary to urgently articulate between economic and political powers in order to establish goals for reducing deforestation in the state, with the purpose of slowing down climate events.